Efficacy and safety of nivolumab combined with standard therapies for first-line therapy of advanced non-small cell lung cancer - Metzenmacher, Martin; Christoph, Daniel C. (Journal of Thoracic Disease, 2016)
In the last 10 years treatment of advanced non-small cell lung cancer (NSCLC) improved and progressed dramatically. Although platinum-based doublet is still state of the art as first-line therapy in most cases (1), patients experience prolonged progression-free survival (PFS) and extended overall-survival (OS) by adding maintenance therapy (2) and/or antiangiogenic drugs (in first- or secondline (3,4) to the cytostatic regime. NSCLC harboring an EGFR-“driver” mutation can be treated effectively, with moderate adverse events, by an oral tyrosine kinase inhibitor (TKI) (5,6) or a combination of TKI with the antiangiogenic drug bevacizumab (7), resulting in improved PFS and OS [in case of an exon 19 deletion (6)].